The Polymorphic Landscape of Halogen Bonded Cocrystals - Hajjar, Christelle (Université d'Ottawa / University of Ottawa, 2022)
Cocrystals have attracted much interest in recent years. It was once thought that cocrystals could be a means to prevent polymorphism but many recent examples of cocrystal polymorphism have been discovered and reported. In this contribution, we present a survey of polymorphic cocrystals. Polymorphism is the ability of a specific chemical compound to crystallize in more than one crystalline form. Polymorphs have different arrangements of the molecules in the given crystal lattice and may exhibit different characteristics such as packing properties, thermodynamic properties, spectroscopic properties, kinetic properties, surface properties, and mechanical properties. Polymorphs can be classified in various groups such as crystalline, amorphous, hydrates, and solvates. The main characterization methods used in this thesis are X-ray diffraction and solid-state NMR spectroscopy. The concept of variable stoichiometry cocrystallization is explored in halogen-bonded systems. Three novel cocrystals of 1,4-diiodotetrafluorobenzene and 3-nitropyridine with molar ratios of 1:1, 2:1, and 1:2, respectively, are prepared by slow evaporation methods. Powder X-ray diffraction experiments carried out on the 1:1 and 2:1 cocrystals confirm that gentle grinding does not alter the crystal forms. 1H → 13C and 19F →13C cross-polarization magic angle spinning (CP/MAS) NMR experiments performed on powdered samples of the 1:1 and 2:1 cocrystals are used as spectral editing tools to select for either the halogen bond acceptor or donor, respectively. I also describe the formation of a new cocrystal of 1, 3, 5-trifluoro-2, 4, 6-triiodobenzene and piperazine with a 2:1 molar ratio that was prepared by the slow evaporation method. In addition of that, I have prepared the cocrystal (1,4- VII diiodotetrafluorobenzene)(coumarin ) already reported. After preparation and purification process of this compound, I obtained a small amount powder, but could not characterize it by solid-state NMR; rather I performed powder X-ray diffraction to study this compound. Overall, this work contributes new examples to the field of polymorphism in halogen-bonded systems and to variable stoichiometry cocrystal engineering with halogen bonds.
Keywords: Cocrystals; Halogen-bonded; polymorphism; solid-state NMR; X-ray diffraction